The Resonance of Unseen Things Poetics, Power, Captivity, and UFOs in the American Uncanny - Lepselter, Susan (University of Michigan Press, 2016)
The Resonance of Unseen Things offers an ethnographic meditation on the "uncanny" persistence and cultural freight of conspiracy theory. The project is a reading of conspiracy theory as an index of a certain strain of late 20th-century American despondency and malaise, especially as understood by people experiencing downward social mobility. Written by a cultural anthropologist with a literary background, this deeply interdisciplinary book focuses on the enduring American preoccupation with captivity in a rapidly transforming world. Captivity is a trope that appears in both ordinary and fantastic iterations here, and Susan Lepselter shows how multiple troubled histories of race, class, gender, and power become compressed into stories of uncanny memory. We really don't have anything like this in terms of a focused, sympathetic, open-minded ethnographic study of UFO experiencers... The author's semiotic approach to the paranormal is immensely productive, positive, and, above all, resonant with what actually happens in history.